IBM Cognos Report Studio as an Effective Tool for Human Capital Reporting - Zinchenko, Yulia (2013)
Main topic discussed in this diploma thesis is corporate reporting in terms of Human Capital using Business Intelligence tools, specifically IBM Cognos Report Studio. One of the objectives is to show step-by-step methodology of creating complex dynamic report, which includes data structure modeling, layout design and quality check. Another objective is to conduct Cost-Benefit Analysis for a real-life project, which is focused on recreating of Excel-based report in Cognos-based environment in order to automate information flows. Essential part of the diploma thesis is theoretical background of Business Intelligence aspects of data quality and visualization as well as purposes of human capital reporting and description of appropriate KPIs. Objectives are addressed by conducting analysis and research of resources related to topics described above as well as using IBM Cognos Report Studio provided by one of the major companies in financial advisory field. This diploma thesis represents relevant reading for those, who are interested in real-life application of data quality improvement and information flow automation using Business Intelligence reporting tools.